Assessing the Effectiveness of the School Learning Action Cell in Addressing Teachers' Needs in Malbug National High School - Labao, Darlon (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the effectiveness of the School Learning Action Cell (LAC) in addressing the professional needs of teachers in Malbug National High School. Anchored on Social Learning Theory, Communities of Practice Theory, and Adult Learning Theory, the study examined teachers’ professional needs in instructional strategies, classroom management, assessment and evaluation practices, curriculum planning and implementation, educational technology, collaboration, administrative support, and monitoring mechanisms. A quantitative descriptive–correlational research design was employed using a researcher-made survey questionnaire administered to forty-six teachers through total population sampling. Frequency count, percentage, weighted mean, and Pearson Product–Moment Correlation Coefficient were used to analyze the data. The findings revealed that most respondents were early to mid-career teachers actively pursuing graduate studies and representing various subject specializations. Teachers moderately needed support in research-based instructional strategies, classroom engagement, assessment literacy, curriculum alignment, and educational technology integration. The School Learning Action Cell was highly implemented in terms of meeting frequency, relevance of topics, collaboration and peer support, administrative support, and monitoring activities. The program was also perceived as very effective in addressing teachers’ professional needs, particularly in collaboration, instructional improvement, and professional growth. Furthermore, a strong positive and statistically significant relationship existed between the level of LAC implementation and its effectiveness, indicating that consistent and well-supported implementation contributes significantly to teacher competence and instructional effectiveness. The study concluded that sustained implementation of the School Learning Action Cell strengthens teacher professional development and enhances teaching practices. It recommends continuous administrative support, strengthened monitoring mechanisms, and sustained professional development activities aligned with teachers’ identified needs. The study supports Sustainable Development Goal 4 (Quality Education) through the promotion of continuous teacher development and improved instructional quality, as well as SDG 8 (Decent Work and Economic Growth) by encouraging lifelong learning and professional growth among educators. The findings also contribute to educational, institutional, and socio-economic sustainability by strengthening collaborative professional development systems in public secondary schools.
Keywords: Administrative Support; Educational Technology; Professional Development; School Learning Action Cell; Teacher Collaboration; Teacher Professional Needs; Teaching Effectiveness